Generation of two induced pluripotent stem cell lines to model and investigate diseases affecting Pacific Islanders - Angela Zhang; James W.S. Jahng; Julio V. Guevara; Christopher D. Yan; Michael V. McConnell; Joseph C. Wu (Stem Cell Research)
Pacific Islanders (PI) comprise only 0.4% of the US population, yet they have amongst the highest prevalence of diseases. They are historically underreported in medical literature and underrepresented in clinical investigation. Increased representation in clinical datasets can mitigate disparities and address differential health outcomes. In recent years, induced pluripotent stem cells (iPSCs) have become a popular platform for disease and drug investigation. Here, we generate two iPSC lines from the peripheral blood mononuclear cells (PBMCs) of healthy PI patients. We demonstrate that the lines exhibit normal morphology and karyotypes, robust expression of pluripotent markers, and the capacity for trilineage differentiation.